Quiste pilonidal gigante en un anciano Giant pilonidal cyst in an elderly man - Héctor Bell Santos; Marcos Antonio Santos Danger (Centro Provincial de Información de Ciencias Médicas, 2011)
Se describe el caso clínico de un anciano con quiste pilonidal gigante, cuya información primaria al respecto se obtuvo de la labor de terreno realizada por su médico de familia y anotada en la historia clínica individual del paciente, el cual fue intervenido quirúrgicamente y con éxito en el Servicio de Coloproctología del Hospital General Docente "Dr. Juan Bruno Zayas Alfonso" de Santiago de Cuba en enero de 2010, cuando se efectuó la exéresis total del tumor sin lesionar el recto. A case report of an elderly man with a giant pilonidal cyst, whose primary data was obtained through a medical visit carried out by the physician of the doctor's office where he belongs and written down in his medical record, is described. This patient was surgically treated with success at the Coloproctology Service from "Dr Juan Bruno Zayas Alfonso" Teaching General Hospital in Santiago de Cuba on January, 2010 when total tumor exeresis was carried out without injuring the rectum.